Chipping free process for combination of narrow saw street (60UM) and thick wafer (600UM) sawing process - Mohd Noh, Mohd Syahrin Amri; Liew, David; Harun, Fuaida (2010)
Chipping free is a dream for wafer sawing process. With current high complexity of wafer technology plus the drive for cost reduction by narrowing the saw street width, it is a challenge which requires huge effort for wafer sawing process to achieve chipping free process. Higher density of metallization causing higher blade loading during mechanical sawing. This leads to chipping penetrating under the guard ring and damaging the active area. This paper will share all the activities towards chipping free process on a device involving optimization through mechanical sawing, infra red camera and laser grooving process. Blade selection involving various diamond grit size, different concentration, slit design and low k types only able to minimize the occurrence but not totally eliminate it. Finally by performing laser grooving, significant results were achieved with zero chipping occurrences. In addition, suitable laser frequency selection is also important to ensure the best performance. In this case higher frequency laser grooving in combination with mechanical sawing process found to be able to meet the requirement.